Local and systemic immune responses in murine Helicobacter felis active chronic gastritis. - Fox, J G (1993)
Helicobacter felis inoculated per os into germfree mice and their conventional non-germfree counterparts caused a persistent chronic gastritis of approximately 1 year in duration. Mononuclear leukocytes were the predominant inflammatory cell throughout the study, although polymorphonuclear cell infiltrates were detected as well. Immunohistochemical analyses of gastric mucosa from H. felis-infected mice revealed the presence of mucosal B220+ cells coalescing into lymphoid follicles surrounded by aggregates of Thy-1.2+ T cells; CD4+, CD5+, and alpha beta T cells predominated in organized gastric mucosal and submucosal lymphoid tissue, and CD11b+ cells occurred frequently in the mucosa. Follicular B cells comprised immunoglobulin M+ (IgM+) and IgA+ cells. Numerous IgA-producing B cells were present in the gastric glands, the lamina propria, and gastric epithelium. Infected animals developed anti-H. felis serum IgM antibody responses up to 8 weeks postinfection and significant levels of IgG anti-H. felis antibody in serum, which remained elevated throughout the 50-week course of the study.